WHY IS PSYCHOLOGY NECESSARY IN LEARNING LANGUAGES - Qarshiboyeva Dilfuza Burliyevna (TADQIQOTLAR.UZ, 2024)
Annotation:  In  this  article  it  is  discussed  about  special  features  between instructors and students especially for future teachers, apart from this, it will be highly explained  about  importance  of  psychology  while  organizing  the  foreign  languages lesson in an efficient way.